2013
DOI: 10.1093/jac/dks535
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline susceptibility in Klebsiella pneumoniae and Escherichia coli causing neonatal septicaemia (2007–10) and role of an efflux pump in tigecycline non-susceptibility

Abstract: The study showed for the first time the trend of tigecycline susceptibility in E. coli and K. pneumoniae causing neonatal septicaemia. Tigecycline still has potent antimicrobial effects against most ESBL- or carbapenemase-producing K. pneumoniae and E. coli, but the increasing MIC values make it essential to be vigilant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 25 publications
1
56
0
Order By: Relevance
“…Tigecycline is another drug that can be considered for the treatment of infections caused by these organisms [35].…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline is another drug that can be considered for the treatment of infections caused by these organisms [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that tigecycline resistance in K. pneumoniae is associated with the overexpression of the acrAB operon (26) (27) . Additionally, a study by Wang et al found there was a statistically significant linear trend in the expression of acrB as the tigecycline MIC increased (14) .…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that only 5 cases had prior use of tigecycline. One study from India also showed that tigecycline nonsusceptibility was not observed among CRKP isolates, and the increase of MIC values of tigecycline was not associated with the use of tigecycline (27). The geographic differences might be responsible for the different resistance phenotype of tigecycline-nonsusceptible K. pneumoniae between Asia and western countries.…”
Section: Discussionmentioning
confidence: 99%